Mengonseptualisasi Prinsip Meaningful Participation Melalui Kerangka Demokrasi Deliberatif Jürgen Habermas: Analisis terhadap Putusan MK No. 91/Puu-Xviii/2020 - Rahmat Mokodompit; Zamroni Abdussamad; Ahmad Ahmad (Indonesian Journal Publisher, 2025)
This article aims to analyze the concept of public participation within Jürgen Habermas’s deliberative democracy framework by focusing on three fundamental rights: the right to be heard, the right to be considered, and the right to be given an explanation. These rights are examined as an integrated deliberative process that links the lifeworld, the public sphere, and the political system. Using a qualitative method with a theoretical approach, this study relies on an extensive literature review to interpret Habermasian deliberative democracy and to explain how citizens’ voices obtain normative legitimacy in democratic decision-making. The findings indicate that the right to be heard highlights the importance of acknowledging citizens’ lived experiences as a moral foundation for public policy. The right to be considered emphasizes the need for an inclusive, domination-free public sphere in which arguments are assessed on equal terms. Meanwhile, the right to be given an explanation underscores the political system’s responsibility to respond to public opinion communicatively rather than merely through formal procedures. The analysis concludes that public participation becomes substantively meaningful only when grounded in communicative rationality and protected from system colonization. Therefore, political legitimacy in modern democracy should not rest solely on procedural compliance but on rational dialogue formed between citizens and the state within a deliberative public sphere.